Effects of morphology of buffer layers on ZnO/sapphire heteroepitaxial growth by RF magnetron sputtering. Issue 1741 (10th February 2015) - Ide, Tomoaki; Matsushima, Koichi; Shimizu, Ryota; Yamashita, Daisuke; Seo, Hynwoong; Koga, Kazunori; Shiratani, Masaharu; Itagaki, Naho
ABSTRACT: Effects of surface morphology of buffer layers on ZnO/sapphire heteroepitaxial growth have been investigated by means of "nitrogen mediated crystallization (NMC) method", where the crystal nucleation and growth are controlled by absorbed nitrogen atoms. We found a strong correlation between the height distribution profile of NMC-ZnO buffer layers and the crystal quality of ZnO films. On the buffer layer with a sharp peak in height distribution, a single-crystalline ZnO film with atomically-flat surface was grown. Our results indicate that homogeneous and high-density nucleation at the initial growth stages is critical in heteroepitaxy of ZnO on lattice mismatched substrates.